Quantification methods comparison in brain (18)F-FDOPA PET - Arena, Julieta E (Am J Nucl Med Mol Imaging, 2019)
(18)F-FDOPA PET is one of the most widely used molecular imaging techniques to assess presynaptic dopaminergic activity. A variety of analytical methods have been developed to quantify (18)F-FDOPA PET images and in most, the striatal-to-occipital ratio (SOR) is used as a quantitative parameter. A manual strategy is typically used for quantification purposes, which can have some caveats, being time-consuming and having some inter-rater variability. In the present study we aimed to test whether automated quantification methods can provide an efficient alternative to manual quantification to overcome its limitations and compare each method’s capacity to discriminate between normal and abnormal subjects. (18)F-FDOPA PET images of 60 subjects were analyzed and quantified with one manual and two automated methods. SUVRs were obtained for caudate and putamen nucleus in both cases. We were able to reach the same level of discrimination with manual and automated strategies, and a threshold for normal/abnormal discrimination could be obtained. We believe automated strategies for VOI quantification can help molecular imaging physicians in the process of interpretation of studies, making the process faster, yet reliable and objective.